Antibacterial Drug Release Electrochemically Stimulated by the Presence of Bacterial Cells – Theranostic Approach. Issue 12 (21st October 2014) - Gamella, Maria; Guz, Nataliia; Mailloux, Shay; Pingarrón, José M.; Katz, Evgeny
Abstract A modified electrode with bioaffinity to E. coli bacterial cells was used to detect bacteria presence on its surface and to produce an electrical signal triggering antibacterial drug release from another coupled electrode. The Sense‐and‐Treat system was realized in two different versions and suggested as the first step to future theranostic applications where bacteria presence results in automatic antibacterial treatment.